Specification for 13 a plugs, switched and unswitched socket-outlets and boxes - British Standards Institution (London BSI, 1967)
Electric plugs, Electric sockets, Electric connectors, Electric pins, Electric terminals, Portable, Dimensions, Design, Marking, Environment (working), Type testing, Testing conditions, Electrical testing, High-voltage tests, Mechanical testing, Deflection tests, Temperature rise, Thermal testing, Leakage paths, Clearance distances, Earthing, Wear tests, Ageing tests, Environmental testing, Drop tests, Impact testing, Fire tests, Tracking tests, Corrosion tests, Pressure testing, Test equipment, Calibration
Revised, Withdrawn
Replacde by BS 1363-1:1984
Keywords: Electric plugs -- Standards